Assistive Technology For Disabilities: A Case Study Of Autism In Teaching And Learning Outcomes - Omar, Sarah; Bidin, Azman; Koo, Ah Choo (2016)

(untitled)
The educational trajectory for future learning methods has changed from traditional learning in the classroom towards assistive technology strategies. The evolution of assistive technologies in the education setting has undergone enormous changes in terms of achieving teaching and learning outcomes, particularly for students with disabilities. A number of studies have highlighted new teaching techniques. There has been a trend in moving towards e-learning technologies in (Agarwal, 2012) and (Kemp, 2015), where those strategies were part of pedagogy techniques in teaching children with special needs. In the past few years, the increase in using assistive technologies such as tablet computers in education to support teaching and learning has led to innovation of more educational computer programs. Young children with Autism Spectrum Disorder (ASD), who suffer from a lack of social communication interaction and understanding of social pragmatisms, such as turn talking in conversation, and difficulty in starting or maintaining conversation between teachers and peers in the classroom, tend to become less communicative.